2021
DOI: 10.3390/separations8070101
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Treatments of Pesticides in Rainwater Runoff by HOCl, O3, and O3/H2O2: Effects of pH, Humic Acids and Inorganic Matters

Abstract: This study systematically investigated the oxidative treatment of five selected pesticides, alachlor (ALA), carbendazim (CAR), diuron (DIU), pyrimethanil (PYR), and tebuconazole (TEB), by comparing their relative reactivities as a function of three different oxidative treatment processes (i.e., chlorine (HOCl), ozone (O3), and ozone/hydrogen peroxide (O3/H2O2)) under various oxidant dosages, reaction times, and pH conditions. For oxidative treatment, pesticide standards were spiked into rainwater. The removal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Yan et al [26] stated that the ozone/peroxymonosulfate (O 3 /PMS)-based technique has a high potential in the treatment of organic wastewater effluents; their investigation found that 85.6% of COD, 81.7% of chromaticity, and 77.6% of dissolved organic carbon (DOC) were removed. Another study found that >49% of alachlor, as an emerging contaminant, was removed by ozone/hydrogen peroxide (O 3 /H 2 O 2 ) [27]. Mojiri et al [28] investigated the performance of integrated electrochemical oxidation and ozonation (EO-O 3 ) in the treatment of wastewater and found that they removed 77% of tonalide and 84.5% of dimethyl phthalate, as PPCPs, and 58.2% of lead (Pb).…”
Section: Treatment Challenges Of Water and Wastewatermentioning
confidence: 99%
“…Yan et al [26] stated that the ozone/peroxymonosulfate (O 3 /PMS)-based technique has a high potential in the treatment of organic wastewater effluents; their investigation found that 85.6% of COD, 81.7% of chromaticity, and 77.6% of dissolved organic carbon (DOC) were removed. Another study found that >49% of alachlor, as an emerging contaminant, was removed by ozone/hydrogen peroxide (O 3 /H 2 O 2 ) [27]. Mojiri et al [28] investigated the performance of integrated electrochemical oxidation and ozonation (EO-O 3 ) in the treatment of wastewater and found that they removed 77% of tonalide and 84.5% of dimethyl phthalate, as PPCPs, and 58.2% of lead (Pb).…”
Section: Treatment Challenges Of Water and Wastewatermentioning
confidence: 99%